Australian students' perspective on interventional radiology education: A prospective cross‐institutional study. Issue 6 (13th July 2018) - Foo, Michelle; Maingard, Julian; Phan, Kevin; Lim, Reuben; Chandra, Ronil V; Lee, Michael J; Asadi, Hamed; Kok, Hong Kuan; Brooks, Mark
Abstract: Introduction: As interventional radiology (IR) adopts an increasingly pivotal role within therapeutic medicine, it is essential that medical students gain exposure to IR so as future doctors, they can fulfil the growing demand for interventional radiologists (IRs) and make appropriate referrals to IRs. Nonetheless, several international studies have reported no or little representation of IR in medical schools. Our study aims to assess the current awareness, exposure, knowledge and attitudes about IR among Australian medical students, so as to provide preliminary data on whether IR teaching in Australian medical schools needs improvement. Methods: A prospective cross‐sectional study was conducted via web‐based and in‐person distribution of a voluntary, anonymous questionnaire. Results: A total of 237 complete responses were received from approximately 1400 clinical‐based students (17% response rate); 38% of respondents had never witnessed an IR procedure, 39% witnessed 1–2 and the remainder, 3–5. Few students reported adequate teaching or knowledge in IR (7% and 5% respectively). Of the 32% of the students considering a career in IR, males predominated (25% of females vs. 59% of males, OR = 0.48, 95%, CI = 0.27–0.83, P  = 0.008). Most students agree that IR should be in the university curriculum (59%) and is key to improving healthcare (74%). Senior students were more likely to report adequate teaching ( P  < 0.001) and believe that IR teaching is important ( P  = 0.001). Conclusions: Australian medical students have a strong appreciation for IR despite having suboptimal teaching, exposure and knowledge in IR. In order to complement and sustain the rapid uptake of IR techniques in modern medicine, university curricula require a greater focus on IR.